Medial Patellofemoral Ligament Reconstruction in Skeletally Immature Patients: A Systematic Review and Meta-analysis. Issue 7 (29th July 2019) - Shamrock, Alan G.; Day, Molly A.; Duchman, Kyle R.; Glass, Natalie; Westermann, Robert W.
Background: Given the proximity of the medial patellofemoral ligament (MPFL) femoral insertion to the distal femoral physis in skeletally immature patients, multiple techniques for femoral graft fixation have been described. Purpose: To systematically review the literature and evaluate outcomes and complications following MPFL reconstruction in skeletally immature patients. Study Design: Systematic review; Level of evidence, 4. Methods: A comprehensive literature search was performed according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines through use of the PubMed, Embase, and Cochrane Central databases. All original, English-language studies reporting outcomes or complications following MPFL reconstruction in skeletally immature patients were included. Skeletally mature patients were excluded. Data regarding demographics, surgical technique, graft type, outcomes, and complications were recorded. Study quality was assessed by use of the modified Coleman methodology score. Statistical analysis was performed through use of chi-square and weighted mean pooled cohort statistics, where appropriate, with significance set at P < .05. Results: 7 studies that entailed 132 MPFL reconstructions (126 patients) met the inclusion criteria. Females comprised 57.9% of the cohort (73 females), and the mean age was 13.2 years (range, 6-17 years). Mean postoperative follow-up was 4.8 years (range, 1.4-10 years). All of the grafts used were autograft, with gracilis tendon (n = 80; 60.6%) being the most common. Methods of femoral fixation included interference screw (n = 52; 39.4%), suture anchor (n = 51; 38.6%), and soft tissue pulley around the medial collateral ligament or adductor tendon (n = 29; 21.9%). Pooled Kujala scores improved from 59.1 to 84.6 after MPFL reconstruction. The total reported complication rate was 25.0% (n = 33) and included 5 redislocations (3.8%) and 15 subluxation events (11.4%). No cases of premature physeal closure were noted, and there were 3 reports of donor site pain (2.3%). Neither autograft choice ( P > .804) nor method of femoral fixation ( P > .416) influenced recurrent instability or overall complication rates. Conclusion: These findings suggest that MPFL reconstruction in skeletally immature patients is a viable treatment option, with significant improvement in patient-reported outcomes and redislocation event rates of less than 5% at nearly 5-year follow-up. Further high-quality research is needed to determine optimal graft options and surgical technique while considering recurrent instability, donor site morbidity, and potential injury to the adjacent physis.